2
$\begingroup$

How to solve the following system of equations? I've tried some basic techniques like adding/substracting and squaring but with no effect. $$ \left\{ \begin{array}{c} \sqrt{1 + x_1} + \sqrt{1 + x_2} + \sqrt{1 + x_3} + \sqrt{1 + x_4} = 2\sqrt{5} \\ \sqrt{1 - x_1} + \sqrt{1 - x_2} + \sqrt{1 - x_3} + \sqrt{1 - x_4} = 2\sqrt{3} \end{array} \right. $$

$\endgroup$
3
$\begingroup$

Let $\mathbf{r}_k= \begin{pmatrix} \sqrt{1+x_{k}} \\ \sqrt{1-x_{k}} \end{pmatrix}$, then $\displaystyle \sum_{k=1}^{4} \mathbf{r}_k= \begin{pmatrix} 2\sqrt{5} \\ 2\sqrt{3} \end{pmatrix}$

Now, \begin{align*} \left| \sum_{k=1}^{4} \mathbf{r}_k \right| &=2\sqrt{5+3} \\ &= 4\sqrt{2} \\ \sum_{k=1}^{4} |\mathbf{r}_k| &= \sum_{k=1}^{4} \sqrt{2} \\ &= 4\sqrt{2} \end{align*}

Considering the inequality $$\left| \sum_{k=1}^{4} \mathbf{r}_k \right| \le \sum_{k=1}^{4} |\mathbf{r}_k|$$

in which equality holds if and only if all $\mathbf{r}_{k}$ are equal.

That is $$4 \begin{pmatrix} \sqrt{1+x_k} \\ \sqrt{1-x_k} \end{pmatrix}= \begin{pmatrix} 2\sqrt{5} \\ 2\sqrt{3} \end{pmatrix}$$

Hence $$\fbox{$x_1=x_2=x_3=x_4=\frac{1}{4}$}$$

$\endgroup$
0
$\begingroup$

HINT:-

Since the roots have to be positive, we see that each radical must reduce to the form $a\sqrt5$ for the first equation , and $b\sqrt3$ for the second equation.

$\endgroup$
2
  • $\begingroup$ Could you please tell something more? I have no idea how to use this observation. $\endgroup$ – XiaoHensZimmer Dec 9 '16 at 16:31
  • $\begingroup$ The $x_i$ are not necessarily rational, so this hint does not apply. $\endgroup$ – Théophile Dec 9 '16 at 19:55
0
$\begingroup$

Denote $$\sqrt{1+x_i}=a_i,~~~\sqrt{1-x_i}=b_i, ~~~(i=1,2,3,4)$$

It's clear that $$a_i,b_i \geq 0,$$and$$a_i^2+b_i^2=2.\tag1$$

Moreover, the system of equations could be rewritten as $$\sum_{i=1}^4a_i=2\sqrt{5},~~~~\sum_{i=1}^4b_i=2\sqrt{3}.\tag2$$

From $(1)$, we have $$\sum_{i=1}^4a_i^2+\sum_{i=1}^4b_i^2=8.$$

From $(2)$, we have $$\left(\frac{1}{4}\sum_{i=1}^4a_i\right)^2+\left(\frac{1}{4}\sum_{i=1}^4b_i\right)^2=2.\tag3$$

But by the inequality $A_n \leq Q_n$, we have

$$\left(\frac{1}{4}\sum_{i=1}^4a_i\right)^2+\left(\frac{1}{4}\sum_{i=1}^4b_i\right)^2 \leq \frac{1}{4}\sum_{i=1}^4a_i^2+\frac{1}{4}\sum_{i=1}^4b_i^2=\frac{1}{4}\left(\sum_{i=1}^4a_i^2+\sum_{i=1}^4b_i^2\right)=2.\tag4 $$

Form $(3)$, we see that the equality holds in $(4)$. Recall the condition for equality in $A_n \leq Q_n$, which is $$a_1=a_2=a_3=a_4,~~~b_1=b_2=b_3=b_4.$$

Thus, we may obtain $$a_i=\frac{\sqrt{5}}{2},~~~b_i=\frac{\sqrt{3}}{2}.$$

As a result, $$x_i \equiv\frac{1}{4},$$ where $i=1,2,3,4.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.